TINJAUAN PENDIDIKAN DAN PELATIHAN UNTUK PEGAWAI NEGERI SIPIL PADA SUATU INSTANSI PEMERINTAH - Kamal, Fahmi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
The development of human resources through education and training is basically a member of the organization in the capacity building work, means of achievement of each employee assessed and measured according to the criteria predefined by the organization. Education and training in government institutions aim to increase the knowledge, expertise, skills and attitudes to be able to carry out the duties of office are prefesional with based on personality and employee ethics. Methods of data collection in this study is the observation and study of literature with qualitative analysis methods. Based on the research results, the implementation of education and training is good enough. Employees who have the education or training to become more skilled in carrying out its work. Education and training is an effort to develop human resources primarily for professional development related to the capabilities and skills of the civil servants. The purpose of this study was to determine how the pattern of education and training provided by a government agency to the ministry, especially civil servants, benefits and objectives. While the usefulness of this study is to add insight, information, and knowledge of employment issues at a government agency, especially at the level of education and vocational training of civil servants. Keywords: Education and Training